Competitive Advantage of Environmental Management and Green Innovation - SISWOYO, MUKARTO; KUSTYADJI, GATOT; WIJAYANI, ARI; HARTATI, WIWI (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Environmentally-based management is a topic that is being widely discussed in various publications. This study uses the mixed method with questionnaire; it is distributed to 110 respondents, also interviewing 3 informants from the management of BUMDES. The result of this study shows that environmental management and green innovation can have a positive and significant effect on the competitive advantage and performance of the company. It is hoped that the result of this study can help the government and BUMDES managers to further develop environmental management and green Innovation.RESUMEN La gestión basada en el medio ambiente es un tema que se está discutiendo ampliamente en varias publicaciones. Este estudio utiliza el método mixto con cuestionario; el mismo se distribuye a 110 encuestados, entrevistándose además a 3 informantes de la gerencia de BUMDES. El resultado de este estudio muestra que la gestión ambiental y la innovación ecológica pueden tener un efecto positivo y significativo en la ventaja competitiva y el desempeño de la empresa. Se espera que el resultado de este estudio pueda ayudar al gobierno y a los gerentes de BUMDES a desarrollar aún más la gestión ambiental y la innovación ecológica.